From "Perverts" to "Fab Five" : the Media's Changing Depiction of Gay Men and Lesbians. - Streitmatter, Rodger (Taylor & Francis, 2008)
From "Perverts" to "Fab Five" tracks the dramatic change in how the American media€has depicted gay people.€ The media, Streitmatter argues, €has not merely reflected the American public's shift to a more enlightened view of gay people, but they have been instrumental in propelling that change.